Direct radiocarbon dates for Vindija G1 and Velika Pećina Late Pleistocene hominid remains - Smith, Fred H. (Array, 1999)
New accelerator mass spectometry radiocarbon dates taken directly on human remains from the Late Pleistocene sites of Vindija and velika Pećina in Hrvatsko Zagorje of Croatia are presented. Hominid speciments from both sites have played critical roles in the development of current perspectives on modern human evolutionary emergance in Europe. Dates of 28 thousand years (ka) before the present (B.P.) and 29 ka B.P. for two speciments from Vindija G1 establish them as the most recent dated Neandertals in the Eurasian range of these archaic humans. The human frontal bone from Velika Pećina, generally considerd one of the earliest representatives of modern humans in Europe, dated to 5 ka B.P., rendering in to longer pertinent to discussions of modern human origins. Apart from invalidating the only radiometrically based example of temporal overlap between late Neandertal and early humans first dispersed into Europe and have implications for the nature and geographic pattering of biological and curtural interactions between these populations and Neandertals.